“Breeding on Mountains” Resulted in the Reorganization of Endophytic Fungi in Asexually Propagated Plants (Ligusticum chuanxiong Hort.) - Kang, Lei; He, Dongmei; Wang, Hai; Han, Guiqi; Lv, Hongyang; Xiao, Wanting; Zhang, Zhanling; Yan, Zhuyun; Huang, Luqi (Frontiers in Plant Science, 2021)
"Mountain breeding, dam area cultivation" is a unique propagation method for the vegetatively propagated plant L. chuanxiong, including two transplants between the mountain and the dam area. It is well known that the environment can regulate the endophytic community structure of plants. However, the change of host endophytic flora caused by transplanting in different places and its influence on asexual reproduction are still poorly understood. We carried out three cycles of cultivation experiments on L. chuanxiong, and collected the stem nodes (LZ), immature rhizomes (PX), medicinal rhizomes (CX) and Rhizosphere. High-throughput sequencing was used to analyze the endophytic fungi in all samples. We observed that the diversity and richness of endophytic fungi in L. chuanxiong increased from transplanting in dam areas to mountain cultivation. Local transplantation caused minor changes in the endophytic fungus structure of L. chuanxiong, while remote transplantation caused significant changes. Compared with LZ after breeding in the dam area, the LZ after mountain breeding has more abundant Gibberella, Phoma, Pericona, Paraphoma, Neocosmospora. The relative abundance of endophytic fungi is consistent with the increase and decrease of the fungus in the soil, and there are also some fungi whose change trends are just opposite to their soil fungi. In addition, there is a significant positive correlation between endophytic fungi no matter in the soil or in the plants. We can conclude that transplantation leads to the recombination of the host endophytic fungus—the more significant the difference in the environment, the greater the reorganization caused by transplanting. The reorganization is determined by the soil native microorganisms, hosts, and the interaction of microorganisms. Remote transplantation is a crucial opportunity to reshuffle the micro-ecological structure of asexual reproduction plants, and regulate plants' growth, development, and resistance and preventing germplasm degradation caused by asexual reproduction.